Evaluation of the Implementation of the Special Allocation Fund Policy in Elementary School Education - Zulfikar, Zulfikar; Lubis, Maksum Syahri; Sembiring, Walid Musthafa (Journal La Sociale, 2025)
This study aims to evaluate the implementation of the Special Allocation Fund (DAK) policy in the field of education, especially in elementary schools, which is applied to improve the quality of educational facilities and infrastructure. DAK is expected to help the government in providing better educational facilities, but its implementation still faces various obstacles. This study uses a qualitative approach with in-depth interview methods and documentation studies as data collection techniques. The results of the study show that the implementation of DAK policies has had a positive impact on the development of elementary school infrastructure, including classroom renovation and the provision of learning tools. However, there are several obstacles faced, including delays in disbursement of funds, lack of transparency in budget management, administrative difficulties, and geographical obstacles that interfere with the smooth implementation of the program. These findings indicate the need to simplify administrative mechanisms and improve coordination between the central government, regions, and schools. In addition, supervision and accountability in the use of funds also need to be improved so that the main objectives of the DAK policy can be achieved optimally. This research is expected to provide useful recommendations for improving the implementation of DAK policies in basic education in the future.